Satellite gravity observation and hydrological modelling-based integrated groundwater storage change in Northwestern India. Issue 2 (4th March 2023) - Pranjal, Pranshu; Chatterjee, R. S.; Kumar, D.; Dwivedi, S.; Jally, Sujit K.; Kumar, Bipin
Abstract: This paper presents a novel approach for an improved estimate of regional groundwater storage (GWS) change in Northwestern India by integrating satellite-based Gravity Recovery and Climate Exchange (GRACE) gravity observation and hydrological modelling of satellite/ in situ hydrometeorological data. Initially, GRACE observation-based terrestrial water storage (TWS) change and hydrological model-based TWS change products were integrated using weight coefficients derived from multi-linear regression analysis of TWS change vs governing hydrological components. Later, the monthly average soil moisture change was subtracted from the monthly average individual and integrated TWS change products to obtain GWS change products. By spatial correlation analysis, three GWS change products were then compared with groundwater level (GWL) fluctuation-based in situ GWS change. Hydrological model, spaceborne GRACE observation, and integrated GWS change products show a positive correlation in ∼59, ∼69, and ∼73% of the area with in situ GWS change. While a hydrological model-based estimate considers geology, terrain, and hydrometeorological conditions, GRACE gravity observation includes groundwater withdrawal from aquifers. All the factors are included in the integrated product. The approach overcomes the limitations of GRACE observation (spatial resolution, geology, terrain, and hydrometeorological factors), hydrological modelling (groundwater withdrawal conditions), and conventional GWL fluctuation-based method (inadequate spatial continuity and cumbersome, labour-intensive exercise). HIGHLIGHTS: An algorithm for estimating improved regional groundwater storage change is proposed by integrating satellite gravity observation and hydrological modelling. Integration weight coefficients are derived by multi-linear regression analysis of TWS change vs governing hydrological components. Hydrological model takes into account geology, terrain, and hydrometeorological factors; GRACE gravity observation includes groundwater withdrawal from the aquifers. Graphical Abstract